The Hydrolysis of Ball-Milled Aluminum–Bismuth–Nickel Composites for On-Demand Hydrogen Generation - Jamey Davies; Stephanus P. Du Preez; Dmitri G. Bessarabov (Energies, 2022)
The hydrolysis of aluminum (Al) is a promising method for on-demand hydrogen generation for low-power proton exchange membrane fuel cell (PEMFC) applications. In this study, Al composites were mechanochemically activated using bismuth (Bi) and nickel (Ni) as activation compounds. The main objective was to determine the effects of Bi and Ni on Al particles during mechanochemical processing, and the hydrolysis activity of the Al-Bi-Ni composites. Successfully formulated ternary Al-Bi-Ni composites were hydrolyzed with de-ionized water under standard ambient conditions to determine the reactivity of the composite (extent of hydrogen production). Scanning electron microscopy (SEM) showed that Bi and Ni were distributed relatively uniformly throughout the Al particles, resulting in numerous micro-galvanic interactions between the anodic Al and cathodic Bi/Ni during hydrolysis reaction. The addition of >1 wt% Ni resulted in incomplete activation of Al, and such composites were non-reactive. All successfully prepared composites had near-complete hydrogen yields. X-ray diffraction (XRD) showed that no mineralogical interaction occurred between Al, Bi, and/or Ni. The main phases detected were Al, Bi, and minute traces of Ni (ascribed to low Ni content). In addition, the effect of the mass ratio (mass Al:mass water) and water quality were also determined.